The impact of economic studies on students’ morality level - Bożena Klimczak (Annales Etyka w Życiu Gospodarczym, 2018)
Since the beginning of the 1980s, a study has been conducted among students of economics in the United States regarding their propensity for cooperation, philanthropy and keeping promises. Regardless of the methods used, the research results have shown lower readiness for cooperation among students of economics in comparison to students of other disciplines. Moreover, the results are even worse after completing a microeconomics course. Based on these findings, two hypotheses have been formulated: the auto-selection hypothesis and the indoctrination hypothesis. The aim of the paper is to formulate implications regarding the indoctrination hypothesis. A massive attendance at economic studies in Poland is an argument against the auto-selection hypothesis. However, unless the research is completed, this hypothesis cannot be rejected. The indoctrination hypothesis is more attractive due to the special cognitive and moral condition of post-communist society which economic studies lecturers are members of and due to the economic situation of higher education institutions. These circumstances which accompany the studying of economics in Poland favour, firstly, the introduction of highly specialised curricula which do not prepare students for understanding economic activity as a means for good life. Secondly, economic knowledge is interpreted by lecturers as a set of instructions to manipulate market players. Thirdly, lecturers’ attitudes and activities reflecting the principle that what is not legally prohibited is allowed are “awarded” with a higher financial status. These implications will be made probable by the analysis of the curricula and content of lectures in economic schools. Attention will be mostly focused on microeconomics; the main “defendant” accused of indoctrination in the American studies.